Adherence to the 24-Hour Movement Guidelines Among Jambi University Sports Education Students: Differences Between Students Who Live in Cities and in Villages - Saputra, Adhe; Muzaffar, Ahmad; Yusradinafi, Yusradinafi (PPSDP International Journal of Education, 2023)
The objective of the study was to compare 24-hour movement guidelines between city-based students and rural students. The study used the survey method with a cross-sectional study approach. The total number of subjects was 40 students with an average age of 20.69 0.83 years, weight 57.32 10.57 kg, and height 169.66 9.78 cm. The findings in the study showed that the students living in the village had met the sleep duration (65%), the duration of screen use (55%), and the physical activity guideline (75%), whereas the city students only met 45% for sleep durations, 20% for screen use, and 35% for 24 hours. Thus, it could be concluded that geographical positioning affects the level of physical activity, so the findings could be used as material for consideration for students to be able to mimic healthy lifestyles that are often applied by students residing in the country in order to balance their fitness status.